2011
DOI: 10.1108/00400911111115672
|View full text |Cite
|
Sign up to set email alerts
|

Both‐and, not either‐or: knowledge and service‐learning

Abstract: Purpose -The purpose of this paper is to expand the understanding of outcomes of service-learning/community engagement. The current study explored the efficacy of service-learning as a pedagogical tool to support content mastery by undergraduates in a management class. Design/methodology/approach -The study involved a classroom experiment with 120 students randomly assigned to complete a service-learning or a research project as a class requirement. Data regarding mastery of course content was collected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…There is a new expectation for schools due to an identified lack of complex problem solving skills in current students who are products of the education system (Casile et al, 2011). With a more modern approach, Leal Filho asserted that successfully educating students to be globally informed and responsible leaders is an indication of the positive outcomes of higher education (as cited in Cress et al, 2010).…”
Section: Transformation Of the Traditional Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…There is a new expectation for schools due to an identified lack of complex problem solving skills in current students who are products of the education system (Casile et al, 2011). With a more modern approach, Leal Filho asserted that successfully educating students to be globally informed and responsible leaders is an indication of the positive outcomes of higher education (as cited in Cress et al, 2010).…”
Section: Transformation Of the Traditional Classroommentioning
confidence: 99%
“…I will remember all of this stuff Science Publications AJEBA much longer than if I'd just done some virtual project or read about something (p. 129). Casile et al (2011) identified that within a group of 90 accounting students, the majority indicated more satisfaction with the course due to service-learning integration. Not only that, but they also felt that they had developed better interpersonal and critical thinking skills.…”
Section: Service-learning In Higher Educationmentioning
confidence: 99%
“…In order to maximise the effectiveness of students' interactions in these committees, students need to be taught the relevant knowledge and skills such as cultural awareness and conflict resolution to enable effective, collaborative relationships in teams (Cress et al, 2001). As shown in previous research, hands-on-learning is more effective in the personal and social development of young people than straight academic application (Casile et al, 2011;Wilson, 2011).…”
Section: Implications For Practicementioning
confidence: 92%
“…Many studies on SL have shown positive outcomes on different personal development aspects, including improved skills on critical thinking, problem solving, communication, enhanced sense of social responsibility and a deeper understanding of learning concept. [2,3,4] Academically, participation in SL has been found to be a predictor of university graduation rates as SL enhances COMMUNITY academic challenge and improves student's timemanagement skills which in turn motivates students to persist in their degree, leading to academic success. [5] Comparing students who are enrolled in SL and non-SL module, the former group engages more in collaborative learning with other students and faculty which further strengthens student's academic growth and assists them to In order to examine the learning outcomes of this new SL subject and whether the intended learning objectives have been met, a qualitative analysis was conducted on the individual reflective journals from students.…”
Section: Introductionmentioning
confidence: 99%